Risk of breast cancer among women with a breastfeeding history of less than two years - Marleni Marleni; Dyah Retnoningrum (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Breast cancer remains a major public health problem among women, with its incidence continuing to increase each year. Breastfeeding is known to have a protective effect against breast cancer; however, a shorter duration of breastfeeding may reduce this protective benefit and increase the risk of disease development. Purpose: To determine the risk of breast cancer among women with a history of breastfeeding for less than two years. Method: An analytical survey with a cross-sectional design was conducted involving 95 respondents selected using probability sampling. Breastfeeding duration was assessed as the independent variable, while breast cancer incidence was the dependent variable. Data were analyzed using the Chi-square test and Prevalence Odds Ratio (POR). Results: The results demonstrated a statistically significant association between breastfeeding duration and breast cancer incidence (p-value = 0.000). Women who breastfed for less than two years were found to have a 9.20-fold higher risk of developing breast cancer compared to those who breastfed for two years or longer (POR = 9.20; 95% CI = 3.55–23.89). Conclusion: A breastfeeding duration of less than two years is a significant risk factor for breast cancer. Strengthening breastfeeding promotion and support for longer duration may serve as an important preventive strategy against breast cancer among women.